Efecto protector de tres diferentes polímeros para la conservación de fresas - Arana Vaca, Luis Antonio (2024)
To prolong the useful life of the strawberry, also known as Fragaria Ananassa, this experimental research seeks to develop three types of coatings based on biopolymers derived from cassava, potato and corn starch. The main objective of this project is to demonstrate that at least one of the treatments is effective in preserving strawberries. To achieve this, analyzes will be carried out on the physical-chemical and microbiological parameters, such as brix degrees, pH and acidity, which are indicators of the fruit's maturity. To evaluate the success of the project, uncoated fruits will be used in addition to the coated strawberries. Likewise, microbiological analyzes will be carried out to determine the microbial load depending on the type of coating used. The strawberries will be subjected to a specific storage period to evaluate their durability based on the treatment that has been applied to them. The InfoStat system will be used for the statistical analysis of the collected data, which will facilitate the comparison of the results obtained in the laboratory. The research will be carried out at the Faculty of Agricultural Sciences of the Technical University of Babahoyo. The application of coatings to extend the shelf life of strawberries is crucial for society, and if the desired results are obtained, it could be an important solution to this problem